Colonial legacy and poverty reduction in sub- Saharan Africa - Rumman Khan; Oliver Morrissey; Paul Mosley (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2016)
Although growth has improved substantially in most African countries in recent years, poverty across the continent has fallen very little in the aggregate. There have been strong poverty reduction performances in some countries, but others exhibit higher poverty rates now than in 1990 despite economic growth. This paper seeks to understand the reasons for this variance; why there are apparently 'two Africas', one with an ability to reduce poverty and one without. The main argument is that some of the reasons for this difference are rooted in colonial times. Countries with strong smallholder cash crop sectors emerged into independence with broad-based labourintensive economies supporting a more equitable income distribution conducive to inclusive growth and poverty reduction compared to initially more inequitable mineral resource and large farm based economies. This did not necessarily determine the post-colonial path: many peasant export economies achieved no poverty reduction (often because of little growth), and some mine/plantation economies did achieve poverty reduction. The key reasons for this evolution lie in the motivation and ability of African elites to form pro-poor coalitions, which in some cases were then able to implement policies supporting a pro-poor pattern of growth.
Keywords: I32; O55; O13; 330; poverty; sub-Saharan Africa; colonial legacy; inclusive growth